Exposure, occurrence, and chemistry of fumonisins and their cryptic derivatives - Braun, Markus S.; Wink, Michael (Comprehensive reviews in food science and food safety, 2018)
Fumonisins are mycotoxins mainly produced by Fusarium proliferatum and Fusarium verticillioides. Because of their wide distribution, the potential health hazard, and economic significance, they are considered one of the most important mycotoxin classes. Epidemiological evidence suggests a relationship between the Fusarium load in corn, exposure to fumonisins, and esophageal cancer. However, mechanisms of actions of fumonisins are not yet fully resolved and epidemiological studies suffer from various confounding factors. Correspondingly, the most relevant congener of the fumonisin family (fumonisin B1) has been classified as possibly carcinogenic to humans and maximum limits have been set for corn and corn-based products. However, many non-corn-based products are also susceptible to fumonisin contamination. Indeed, some of them contain very high amounts of fumonisins, but enter the market legally. Furthermore, fumonisin exposure of consumers is probably consistently being underestimated because only a fraction of fumonisins can be detected by routine analysis. The bioavailability and toxicity of most nondetectable (cryptic) forms has not been resolved. In this work, we review the developments of cancer research into fumonisins since their discovery in 1988 until today and provide an overview of the contributions of various foodstuffs to fumonisin exposure, including those products that have been largely neglected in the past. In conclusion, (1) corn remains the principal source of fumonisin ingestion, but fumonisins in non-corn-based commodities require continuous monitoring; (2) cryptic fumonisins should be included in risk assessment studies; and (3) certain population groups (for example children) may suffer from enhanced exposure and could face increased health risks.
Gesehen am 06.08.2019